1948
DOI: 10.1017/s0022172400036251
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of typhoid fever in the Middle East

Abstract: 1. An outbreak of typhoid fever in a Royal Air Force camp in the Middle East is discussed.2. A total of 110 cases occurred of which 105 are analysed. The case-fatality rate was 10%.3. Of the 105 cases 59% gave a positive blood culture. The percentages of diagnostic isolations from stools and urine were small.4. Clearance tests of stools and urine showed that 8.4% of patients excreted Salm. typhi during convalescence.5. Leucocyte counts during the first 2 weeks of the illness showed that only 30% of the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1951
1951
1991
1991

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…The conclusions drawn from findings in the investigation described agree with those of Anderson & Richards (1948) that a high 'Vi' titre was not invariably associated with a temporary carrier state and that high titres were occasionally found in convalescence in the absence of a demonstrable carrier state. These conclusions, however, differ from those of Bhatnagar (1944) who considered that the presence of 'Vi' agglutinins was invariably associated with the presence of S. typhi within the body.…”
Section: Carriers Resulting From the Outbreaksupporting
confidence: 84%
See 2 more Smart Citations
“…The conclusions drawn from findings in the investigation described agree with those of Anderson & Richards (1948) that a high 'Vi' titre was not invariably associated with a temporary carrier state and that high titres were occasionally found in convalescence in the absence of a demonstrable carrier state. These conclusions, however, differ from those of Bhatnagar (1944) who considered that the presence of 'Vi' agglutinins was invariably associated with the presence of S. typhi within the body.…”
Section: Carriers Resulting From the Outbreaksupporting
confidence: 84%
“…The findings with regard to the titres of 'Vi' agglutinins extend the observation of Anderson & Richards (1948) in that out of 303 non-immunized patients followed up after discharge, 196 (64.6%) still had demonstrable 'Vi' agglutinins present 12-24 months after discharge.…”
Section: Sera From Immunized Nursessupporting
confidence: 79%
See 1 more Smart Citation
“…vaccine before the necessary precautions in the handling of the vaccine had been introduced. This applies also to the observations on the value of the alcoholized vaccine recorded by one of us in a report on an outbreak of typhoid fever in the Middle East in 1945 (Anderson & Richards, 1948).…”
mentioning
confidence: 60%
“…Approximately 30% of patients may still excrete Salmonella typhi immediately after completing treatment, but almost 90% of those become negative within one month (Vogelsang and B0e, 1948). Anderson and Richards (1948) found that all nine convalescent excreters out of 110 cases cleared spontaneously. However, usually about 3% of patients contracting typhoid fever become chronic carriers-that is, they are found to be excreting Salm.…”
Section: Discussionmentioning
confidence: 96%